Task Aversiveness Sebagai Prediktor Prokrastinasi Akademik Pada Mahasiswa - Nike Isma Putri; Triana Noor Edwina (Jurnal Studi Guru dan Pembelajaran, 2020)
This study was designed to investigate the relationship between task aversiveness and academic procrastination in Postgraduate students at Mercu Buana University, Yogyakarta. The population of this study consists of three study programs, namely Masters in Psychology, Masters in Professional Psychology and Masters in Food Sciences, totaling 301 students. The sampling technique used was disproportionate stratified random sampling. The number of samples used in this study 172 students. The data collection method used is a scale method in the form of a Likert scale. The scale of task aversiveness of researchers is based on the theory of task aversiveness according to Blunt & Pychyl (2000) and the academic scale of academic procrastination is based on the theory of procrastination according to Ferrari, et al. (1995). The hypothesis test used is the product moment correlation. The hypothesis of this study is that there is a positive relationship between task aversiveness and academic procrastination in students. The purpose of this research is expected to make a scientific contribution to the development of the world of psychology, especially educational psychology by looking at the factors that contribute to academic procrastination.